Extraordinary daytime only urinary frequency in childhood: Prevalence, diagnosis, and management. Issue 2 (April 2018) - Marzuillo, Pierluigi; Diplomatico, Mario; Marotta, Rosaria; Perrone, Laura; Miraglia del Giudice, Emanuele; Polito, Cesare; La Manna, Angela; Guarino, Stefano
Summary: Introduction: Since standardization of the ICCS terminology, only two small case series of children with extraordinary daytime only urinary frequency (EDOUF) have been published. The aims of the present study were i) to describe a large cohort of children affected by EDOUF, to evaluate its rate among the main micturition pediatric disturbances, and to determine if there is different EDOUF onset among seasons; ii) to investigate possible associations with urodynamic abnormalities by non-invasive techniques; iii) to evaluate whether postponing micturition exercise (PME) can objectively verify the anamnestic data hinting at the EDOUF diagnosis; and iv) to determine the effect of postponing micturition at home. Material and methods: We reviewed the records of all patients with EDOUF, nocturnal enuresis, and/or overactive bladder firstly examined from March 2012 to February 2016. We evaluated post-void residual and bladder wall thickness by urinary ultrasound and uroflowmetry and recorded the season in which the EDOUF started. Through the PME, the EDOUF diagnosis was confirmed if patients were able to postpone micturition reaching at least 80% of the expected bladder capacity without showing urinary incontinence. At home, we recommended postponing micturition for a maximum of 3 h if EDOUF affected the normal daily activities of both children and parents. We set a telephone interview for 3 months later. Results: The clinical characteristics of the EDOUF population are shown in the Table. The EDOUF rate was 12.1%. The rate of EDOUF onset was significantly lower during the summer than in other seasons ( p  = 0.02) and the OR for onset of EDOUF in the summer – compared with the other seasons – was 0.37 (95% CI 0.18–0.74; p  = 0.005). Eighty-five (80.2%) patients reported an intermittent trend of the EDOUF with variable periods of improvement and worsening. All the EDOUF patients had normal uroflowmetry, 1/106 had post-micturition bladder wall thickness >5 mm and one post-void residual. At the PME, 106 out of 106 (100%) patients with EDOUF were able to reach at least 80% of the EBC without showing urinary incontinence or urgency incontinence. After 3 months, in 98.1% of the patients the symptoms had disappeared or improved. Discussion and conclusions: Childhood EDOUF is rather common and is generally associated with normal non-invasive urodynamic patterns. The PME allows verification of anamnestic data of EDOUF. The sole recommendation to postpone micturition for a maximum of 3 h or until the micturition postponement became stressful could be considered as a possible approach. Table Clinical characteristics of the 106 patients with EDOUF. Age at EDOUF diagnosis, yr 6.8 ± 2.3 Female sex, no. (%) 53 (50) SBP, SDS 0.31 ± 0.7 DBP, SDS 0.17 ± 0.8 Age at continence, yr 2.3 ± 0.5 Nocturia, no. (%) 1 (0.9) Constipation, no. (%) 19 (17.4) Urgency, no. (%) 0 (0) Incontinence, no. (%) 0 (0) EBC >80% at PME, no. (%) 106 (100) Post-micturition bladder wall thickness >5 mm, no. (%) 1 (0.9) Presence of post-void residual, no. (%) 1 (0.9) a Maximum flow, mL/s 19.34 ± 10.2 Normal uroflowmetry, no. (%) 106 (100) Normal urinalysis, no. (%) 106 (100) Previous UTIs, % 2 (1.9) b Daily micturitions, no. 20.1 ± 7.2 Mean daily voided volumes (% of the EBC) 28.7 ± 9.2 Data are given as means ± SDS, unless stated otherwise. DBP, diastolic blood pressure; EBC, expected bladder capacity; EDOUF, extraordinary daytime only urinary frequency; PME, postponing micturition exercise; SBP, systolic blood pressure; SDS, standard deviation score; UTI, urinary tract infection. a Only one patient presented a post-void residual of 30 mL. b All the UTIs were not febrile.